Strategi Pengelola Sekolah Swasta dalam Menghadapi Persaingan - Dwi Putri, Ariska; Saraswati, Indriani; Fitriyah, Nina (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
This research presents an in-depth literature review to explore the effectiveness of private school management strategies in facing competition in the education domain. The purpose of this study is to analyze and synthesize recent findings related to private school management strategies, with a focus on how schools can improve their competitiveness. The research method involved reviewing a number of empirical studies, academic articles and other relevant literature. The results identified several key factors that contribute to the effectiveness of management strategies, including the adoption of innovative business models, financial sustainability, efficient human resource management and active involvement in educational community building. The conclusion of this literature review is that private schools that adopt evidence-based strategies and are responsive to environmental changes can achieve sustainable competitive advantage. The importance of technology adoption in the management process is also prominent in the literature. Therefore, further research and practical implementation are needed to further understand the dynamics and applications of private school management strategies in facing competition in the modern education era.